Effect of lurasidone on meaningful change in health-related quality of life in patients with bipolar depression. (May 2016) - Calabrese, Joseph; Rajagopalan, Krithika; Ng-Mak, Daisy; Bacci, Elizabeth D.; Wyrwich, Kathy; Pikalov, Andrei; Loebel, Antony
Abstract : Estimate the proportion of lurasidone-treated patients with bipolar depression who achieved a clinically meaningful improvement in health-related quality of life (HRQoL) as measured by the Quality of Life Enjoyment and Satisfaction Questionnaire Short Form (Q-LES-Q SF). A post-hoc analysis of data from two 6-week, randomized, placebo-controlled clinical trials of lurasidone as monotherapy (20–60 or 80–120 mg/day) or adjunctive therapy (20–120 mg/day) was carried out. The proportion of patients with clinically meaningful HRQoL improvement at 6 weeks was assessed using the following methods: an anchor-based method using a one-point improvement on the Clinical Global Impression-Severity, Bipolar Version (CGI-BP-S) scale; a distribution-based method using Q-LES-Q SF's SEM; and cumulative distribution functions. Data from 364 and 275 patients were available from the monotherapy and adjunctive therapy trials, respectively. Using anchor-based thresholds, a significantly higher proportion of lurasidone-treated patients reported a clinically meaningful improvement in HRQoL versus placebo in monotherapy (65.0% and 62.5 vs. 41.1%, both P <0.01) and adjunctive therapy (65.2 vs. 50.7%, P <0.05). Similar findings were observed using distribution-based thresholds for monotherapy (82.5% and 78.3 vs. 58.1%, both P <0.01) and adjunctive therapy (74.5 vs. 62.7%, P <0.05), and through the visual display of cumulative distribution functions. Short-term lurasidone monotherapy and adjunctive therapy is associated with a clinically meaningful improvement in HRQoL in patients with bipolar depression.